2016
DOI: 10.1038/nature19789
|View full text |Cite
|
Sign up to set email alerts
|

A cholinergic basal forebrain feeding circuit modulates appetite suppression

Abstract: Atypical food intake is a primary cause of obesity and other eating and metabolic disorders. Insight into the neural control of feeding has previously focused mainly on signalling mechanisms associated with the hypothalamus1-5, the major centre in the brain that regulates body weight homeostasis6,7. However, roles of non-canonical central nervous system signalling mechanisms in regulating feeding behaviour have been largely uncharacterized. Acetylcholine has long been proposed to influence feeding8-10 owing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 29 publications
4
134
1
Order By: Relevance
“…Thus, one main function of cholinergic neurons may be to act as a teaching and alerting signal to the cortex in the presence of behaviorally important stimuli. Caudal projections of BF cholinergic neurons whose cell bodies are located in the diagonal band are also reward-related since they modulate appetite [38]. …”
Section: How Do They Behave?mentioning
confidence: 99%
“…Thus, one main function of cholinergic neurons may be to act as a teaching and alerting signal to the cortex in the presence of behaviorally important stimuli. Caudal projections of BF cholinergic neurons whose cell bodies are located in the diagonal band are also reward-related since they modulate appetite [38]. …”
Section: How Do They Behave?mentioning
confidence: 99%
“…Memory and learning have long been appreciated as important influences on food intake and preferences [64]. Recent evidence suggests that impaired cholinergic signaling resulted in hyperphagia and severe obesity, whereas stimulation of cholinergic DBB neurons suppressed food intake in mice [65]. In patients with Alzheimer’s disease, deep brain stimulation of the NBM resulted in nutritional status stabilization in a 1-year period [66].…”
Section: Discussionmentioning
confidence: 99%
“…As will be discussed later, they likely play an important role in mediating cue-related anticipatory feedforward inhibition of ARC AgRP neurons (Betley et al, 2015; Chen et al, 2015; Mandelblat-Cerf et al, 2015). Finally, it was recently shown that cholinergic neurons in the forebrain suppress appetite (Herman et al, 2016). Strikingly, impairment of their function causes marked hyperphagia and obesity.…”
Section: Section 3: Hypothalamic Regulation Of Hunger/satietymentioning
confidence: 99%
“…Strikingly, impairment of their function causes marked hyperphagia and obesity. The ability of these cholinergic neurons to control appetite appears to be mediated, at least in part, by projections to the arcuate, where released acetylcholine (Ach) may engage AChRs on ARC POMC neurons and/or possibly ARC Glutamatergic neurons (Herman et al, 2016; Mineur et al, 2011). The function of such forebrain cholinergic regulation is not presently understood.…”
Section: Section 3: Hypothalamic Regulation Of Hunger/satietymentioning
confidence: 99%
See 1 more Smart Citation